Modulated circulation control around the blades of a vertical axis hydrokinetic turbine for flow control and improved performance. (May 2019) - Gorle, J.M.R.; Chatellier, L.; Pons, F.; Ba, M.
Abstract: The circulation control around the Darrieus turbine blades is considered as a significant practical solution so as to improve the machine's performance. This paper describes a kinematics-based method, through which the pitching motion of the blades varies in such a way that the flow is controlled around them as well as across the rotor. For this purpose, the potential flow approach is used to derive the blade pitching laws being compatible with the unsteady Kutta-Joukowski condition at the trailing edge of the blade. By means of this, a constant circulation around the blade is ensured. Preliminary CFD investigations have evidenced the operating conditions at which the constant-circulation framework may be applied to turbulent flows in order to control the vortex shedding and avoid blade-vortex interactions. Nonetheless, a strict application of this concept prevents the turbine from harvesting the energy. As an alternative strategy, the application of a locally variable-circulation is proposed in order to enhance the power output without compromising on flow control. Three major accomplishments of the variable-circulation-based blade pitching proposition are the following: a. flow control around the turbine blades with definite patterns of vortical structures, b. consistent increase in the turbine's coefficient of power, and c. widened operating range of the turbine. Highlights: Kinematics-based blade pitching laws for a hydrokinetic turbine are developed. Power characteristics deteriorate with a constant circulation around the blades. Piecewise circulation laws optimise the power output without compromising on flow control. Definite patterns of vortical structures allow to install the turbines in arrays.